From small molecules to nano-scale architectures - a supramolecular approach - Scott, Benjamin M. T. (Kansas State University, 2008)
We have shown that supramolecular synthons can be used to construct discrete two or three component co-crystals and 1-D inorganic-organic chains and dramatically influence the arrangement of nanoparticle assemblies. A collection of supramolecular reagents (SR's) have been designed and synthesised to carry out a systematic study into hydrogen bonding. In order to test Etter's guideline "the best proton donor and acceptor remaining after intramolecular hydrogen-bond formation will form an intermolecular hydrogen-bond" and to develop a hierarchy of interactions, a series of co-crystals between the supramolecular reagents and hydrogen-bond donors (carboxylic acids) have been synthesised. Co-crystals with pyrazole benzamide SR's have demonstrated the ability to fine-tune hydrogen-bond formation. By utilising a poor hydrogen-bond acceptor (pyrazole) the incoming carboxylic acid opts to form a heteromeric acid-amide dimer via N-H[three dots]O hydrogen bonds. Additionally, we have shown that the hydrogen-bond acceptor strength of the pyrazole can be turned up through simple covalent modifications (i.e. isomer change or addition of methyl groups to the pyrazole ring). Although the heteromeric acid-amide dimer is observed, O-H[three dots]N hydrogen bonds to the pyrazole are also observed in cases when more than one donor site is present (i.e. di-carboxylic acids and 4-hydroxybenzoic acid). Furthermore, co-crystals with picolyl-indazole and pyrimidine-pyrazole SR's agree with Etter's guideline. In all cases, the incoming carboxylic acid forms an O-H[three dots]N hydrogen bond to the best acceptor (pyridine and pyrazole, respectively). The homomeric amide-amide dimer has been used to construct inorganic-organic hybrid materials. The reaction between the pyrazole benzamide ligands with acac or "paddle-wheel" complex ions yielded 1-D chains. Furthermore, pyrimidine-bispyrazole and functionalised 1,3-bisbenzylpyrazole ligands have been utilised as chelating-ligands for reliable metal coordination. Finally, the power of supramolecular synthons to control the arrangement of much larger nanoparticle assemblies has been shown. Both homomeric (acid-acid, alcohol-alcohol) and heteromeric (acid-imidazole, alcohol-imidazole) hydrogen bonding cause significant changes in nanoparticle assemblies.
Keywords: Supramolecular; Nano; Pyrazole; Supermolecule; Heterocycle; Chemistry, General (0485); Chemistry, Inorganic (0488); Chemistry, Organic (0490)